Down-regulation of circ0001361 induces apoptosis and suppresses the progression of glioma - Xiaoqiong Zou; Ping Wang; Weixia Nong; Chang Liu; Feng Li; Chunhong Xue; Xin Li; Yanjing Wang; Yingying Ge; Qingmei Zhang; Bin Luo; Xiaoxun Xie (PLoS ONE, 2026)
Background Circ0001361 is a novel circRNA identified by our previous high-throughput sequencing of glioma. Here we explored the functional involvement of circ0001361 in gliomagenesis and elucidated its potential molecular mechanisms. Methods The expression of circ0001361 in glioma was determined by qRT-PCR. CCK-8, colony formation assay, wound-healing, transwell assay, flow cytometric analysis and western blot were conducted to investigate cell proliferation, migration, invasion and apoptosis. The potential target miRNAs of circ0001361 and their downstream mRNAs were predicted by bioinformatics analysis and validated using dual-luciferase reporter assays. Results Elevated expression of circ0001361 were observed in glioma tissues. The expression of circ0001361 was positively correlated with WHO tumor grades and Ki67 index, a well-established proliferation biomarker. Functional assays demonstrated that circ0001361 depletion inhibited cell proliferation, migration and invasion, while it promoted apoptosis. The bioinformatics analysis revealed that circ0001361 might target hsa-miR-525-5p, and further indicated that MEIS1 was a predicted downstream target of hsa-miR-525-5p. Subsequently, these predicted targeting relationships were both confirmed by dual-luciferase reporter assays. Conclusion Circ0001361 enhances tumorigenic properties. Mechanistically, circ0001361 may regulate glioma progression via hsa-miR-525-5p/MEIS1, suggesting its potential as a therapeutic target for glioma intervention strategies.